Maximum Harm : The Tsarnaev Brothers, the FBI, and the Road to the Marathon Bombing - McPhee, Michele (Book collections on Project MUSE., 2017)
"Michele R. McPhee unravels the complex story behind the public facts of the Boston Marathon bombing. She examines the bombers' roots in Dagestan and Chechnya, their struggle to assimilate in America, and their growing hatred of the United States. The difficulties faced by the Tsarnaev family of Cambridge, Massachusetts, are part of the public record. Circumstances less widely known are the FBI's recruitment of the older brother, Tamerlan Tsarnaev, as a 'mosque crawler' to inform on radical separatists here and in Chechnya; the tracking down and killing of radical Islamic separatists during the six months he spent in Russia--travel that raised eyebrows, since he was on several terrorist watchlists; the FBI's botched deals and broken promises with regard to his immigration; and the disenchantment, rage, and growing radicalization of Tamerlan and Dzhokhar, along with their mother, sisters, and Tamerlan's wife, Katherine. Maximum Harm is also a compelling examination of the Tsarnaev brothers' movements in the days leading up to the Boston Marathon bombing on April 15, 2013, the subsequent investigation, the Tsarnaevs' murder of MIT police officer Sean Collier, the high-speed chase and shootout that killed Tamerlan, and the manhunt in which the authorities finally captured Dzhokhar, hiding in a Watertown backyard. McPhee untangles the many threads of circumstance, coincidence, collusion, motive, and opportunity that resulted in the deadliest attack on the city of Boston to date."--Provided by publisher.